The The Application of Silver Nanoparticles Synthesized Using Moringa Leaf extract for the Detection Mercury (II) Metal Ions - Siregar, Nonny Cristine; Yanti, Demi Dama; Ashari, Arif; Aji, Abdul; Indarto, Indarto (Department of Chemistry - Universitas Bangka Belitung, 2025)
The increasing demand for clean water sources aligns with the continuous growth of the human population and environmental challenges. Water is a fundamental necessity for sustaining life, and its quality must be maintained to ensure safe utilization. However, contamination by heavy metals significantly degrades water quality, rendering it unsuitable for human consumption and daily use. Among various detection methods, silver nanoparticles (AgNPs) have emerged as promising nanomaterials for identifying the presence of heavy metal ions in water sources, including mercury (II) ions (Hg²⁺). The detection mechanism is based on colorimetric changes that can be further analyzed using UV-visible spectrophotometry. In this study, silver nanoparticles were successfully synthesized via a green synthesis approach using Moringa oleifera leaf extract as a bioreducing agent. The optimal synthesis conditions were established at a precursor concentration of 2.5 mM, a reaction temperature of 50°C, and a synthesis duration of 90 minutes. The resulting AgNPs exhibited an average particle size of 103.8 nm and demonstrated stability for up to three days. Furthermore, the synthesized AgNPs showed high sensitivity in detecting mercury (II) ions at concentrations as low as 20 ppm, highlighting their potential application in water quality monitoring and environmental remediation.